Critical AI Literacy Development in Business Schools: An Interiority-Infused Action Research Framework for Collective Empowerment - Futonge Nzembayie, Kisito (Emerald Publishing Limited, 2025)
Generative AI (Gen AI) is emerging as a transformative general-purpose technology with significant societal implications, pressing higher education institutions to integrate critical AI literacy into staff and student development. However, the approach to developing and implementing such literacy in business schools remains a topic of ongoing debate. Using insider action research in a process of planned change management, this study explores an AI transformation initiative at a leading Irish business school, identifying the mechanisms that effectively contribute to, and impede critical AI literacy development. Through abductive analysis, the research elucidates the value of developing critical AI literacy through infusing interiority in an action research framework - with "interiority" denoting the integration of theoretical, practical, and relational knowing towards enhanced intellectual self-awareness and self-empowerment. The study contributes by offering an interiority-infused action research framework as a conceptual tool to guide the development of AI transformation initiatives leading to critical AI literacy.
Research in Organizational Change and Development -ROCD Volume 31
PUBLISHED
Keywords: AI Literacy, Interiority, Insider Action Research, Management Education, Learning Mechanisms, Digital Transformation; Digital Engagement; Digital Humanities; Digital Platform; Future of Management Education; Human Resource Management; Management Education